Mobile applications development with Android technologies and algorithms - Qiu, Meikang; Dai, Wenyuan 1983-; Gai, Keke (CRC Press, 2017)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- List of Figures -- List of Tables -- Preface -- Acknowledgments -- Author Biographies -- SECTION I: Mobile App Design and Development Skills -- CHAPTER 1: Overview of Mobile App and Mobile Interface -- 1.1 MOBILE SYSTEM -- 1.2 MOBILE INTERFACE AND APPLICATIONS -- 1.2.1 Optimizations in Mobile Systems -- 1.2.2 Mobile Embedded System -- 1.3 MOBILE CLOUD -- 1.3.1 Big Data Application in Mobile Systems -- 1.3.2 Data Security and Privacy Protection in Mobile Systems -- 1.3.3 Concept of Mobile Apps
Keywords: Electronic books